Spontaneous repositioning of a dislocated autologous scleral plug after vitrectomy with autologous scleral plug for optic disc pit maculopathy: A case report - Yong Koo Kang; Seonyong Jeong; Dong Ho Park; Jae Rock Do (American Journal of Ophthalmology Case Reports)
Purpose: Presented herein is a case of optic disc pit maculopathy (ODP-M) treated with vitrectomy and autologous scleral plug implantation, complicated by scleral plug dislocation. The dislocation was subsequently corrected by spontaneous repositioning without surgical intervention. Observations: A 58-year-old female was diagnosed with ODP-M and underwent vitrectomy with internal limiting membrane peeling and autologous scleral plug implantation. Postoperatively, the scleral plug successfully sealed the ODP. There was an improvement in visual acuity and a decrease in subretinal fluid (SRF) and cystoid macular edema (CME). Seven weeks after surgery, dislocation of the scleral plug was observed, which was associated with frequent upside-down positioning using an inverting table. The patient was instructed to maintain a supine position, which resulted in spontaneous repositioning of the scleral plug. The scleral plug remained stable over 10 months postoperatively, with continued resolution of CME and SRF. Visual acuity improved to 20/25. Conclusions and importance: Upside-down positioning may lead to scleral plug dislocation following autologous scleral plug implantation for ODP-M and should be avoided. However, in cases of dislocation, maintaining a supine position may facilitate spontaneous repositioning, potentially eliminating the need for additional surgery. This case underscores the importance of patient education regarding postoperative positioning and demonstrates the potential effectiveness of positional management for scleral plug dislocation.